Forecasting investments in fixed assets - A. M. Terekhov (Вестник университета)
The article details the issues of forecasting investments in fixed assets. The theoretical aspects (foreign experience) of using various forms of predictive models based on the analysis of foreign scientific literature are considered. Two different forecasting methods have been practically implemented using the example of building multiplicative and ARIMA models. Quarterly forecasts of the cost of investments in fixed assets for 2022–2023 in the Russian Federation are formulated. A comparison of the simulation results showed that the calculated values for both models describe the dynamics of the indicator well, the forecast values differ, and therefore an average (combined) forecast is built based on the prediction results for both implemented methods. The results of the study can be used in the practical activities of state and municipal bodies, enterprise management for quarterly forecasting of investments in fixed assets.